Bi-Hormonal Endocrine Cell Presence Within the Islets of Langerhans of the Human Pancreas Throughout Life - Jiwon Hahm; Dawn Kumar; Juan Andres Fernandez Andrade; Edith Arany; David J. Hill (Cells)
Bi-hormonal islet endocrine cells have been proposed to represent an intermediate state of cellular transdifferentiation, enabling an increase in beta-cell mass in response to severe metabolic stress. Beta-cell plasticity and regenerative capacity are thought to decrease with age. We investigated the ontogeny of bi-hormonal islet endocrine cell populations throughout the human lifespan. Immunofluorescence microscopy was performed for insulin, glucagon, and somatostatin presence on paraffin-embedded sections of pancreata from 20 donors without diabetes aged between 11 days and 79 years of age. The mean proportional presence of glucagon-, insulin-, and somatostatin-immunoreactive cells within islets was 27.5%, 62.1%, and 12.1%, respectively. There was no change in the relative presence of alpha- or beta-cells with advancing age, but delta-cell presence showed a decline with age (R2 = 0.59, p < 0.001). The most abundant bi-hormonal cell phenotype observed co-stained for glucagon and insulin, representing 3.1 ± 0.3% of all islet cells. Glucagon/somatostatin and insulin/somatostatin bi-hormonal cells were also observed representing 2–3% abundance relative to islet cell number. Glucagon/insulin bi-hormonal cells increased with age (R2 = 0.30, p < 0.05) whilst insulin/somatostatin (R2 = 0.50, p < 0.01) and glucagon/somatostatin (R2 = 0.35, p < 0.05) cells decreased with age of donor. Findings show that bi-hormonal cells are present within human pancreatic islets throughout life, perhaps reflecting an ongoing potential for endocrine cell plasticity.